1983
DOI: 10.1073/pnas.80.7.2086
|View full text |Cite
|
Sign up to set email alerts
|

Action potentials and membrane ion channels in clonal anterior pituitary cells.

Abstract: The electrophysiological properties of the mouse anterior pituitary cell line AtT-20/D16-16 were investigated with intracellular and patch-clamp techniques. Clonal AtT-20/D16-16 cells were found to be electrically excitable, with most cells exhibiting spontaneous bursting action potentials. The mean burst rates varied from 1.4 Hz at -55 mV to 8.2 Hz at -25 mV, showing an approximately linear frequency-current relationship in the low current range. The bursts consisted of one to several fast Na4 spikes superimp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 30 publications
4
45
0
Order By: Relevance
“…IA c). As previously reported (Adler et al 1983 (Fig. 1 C, open symbols) Step potential (mV) simultaneously with perforated patch recording and fluorescence photometry.…”
Section: C1-current Action Potentials and Ca2+ Influxsupporting
confidence: 60%
See 2 more Smart Citations
“…IA c). As previously reported (Adler et al 1983 (Fig. 1 C, open symbols) Step potential (mV) simultaneously with perforated patch recording and fluorescence photometry.…”
Section: C1-current Action Potentials and Ca2+ Influxsupporting
confidence: 60%
“…Both acutely dissociated and clonal anterior pituitary cells spontaneously fire Ca2+ action potentials (Kidokoro, 1975;Taraskevich & Douglas, 1987; Suprenant, 1982;Adler, Wong, Sabol, Busis, Jackson & Weight, 1983;Mollard, Vacher, Guerin, Rogowski & Dufy, 1987;Schlegel, Winiger, Mollard, Vacher, Wuarin, Zahnd, Wollheim & Dufy, 1987). One mechanism by which secretion is thought to be controlled is by modulation of Ca2+ influx though voltagegated Ca2+ channels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 3-adrenergic agonists enhance the frequency of action potential generation in AtT-20 cells, which has been associated with an increase in transient calcium currents across the cell membrane (9,10). This increase in calcium currents has been correlated with the ability of 3-adrenergic agonists to release ACTH from these tumor cells (9,10).…”
Section: Resultsmentioning
confidence: 99%
“…8-Adrenergic agonists, which stimulate cAMP-dependent protein kinase activity and the secretion of ACTH from AtT-20 cells (7), also depolarize AtT-20 cells and increase the frequency of action potentials in these corticotrophs (9,10). This electrical activity has been associated with transient calcium currents (9,10), and (3-adrenergic agonists and forskolin, a direct activator at adenylate cyclase, increase cytosolic calcium levels in AtT-20 cells (11). In addition to cAMP and calcium, activators of protein kinase C evoke ACTH release (12), and recent studies (13) have suggested a role for phosphatidylinositol turnover in hormone secretion from corticotrophs.…”
mentioning
confidence: 99%